(untitled) (International Journal of Physiotherapy, 2018)
Background: Scapular dyskinesis, or abnormal scapular dynamic control, is a condition which is associated with athletes presenting with shoulder pathology, although it is also found in asymptomatic individuals. Studies differ on whether it is a cause or a symptom of shoulder pain. There is currently no research on whether treating scapular dyskinesis prior to the onset of pain by prehabilitation will stop the progression of pain in asymptomatic water polo players. Methods: This study was a prospective randomized controlled trial. Twenty-five male water polo players were screened for scapular dyskinesis, and 22 players were included in the study after having a positive finding. The Closed Kinetic Chain Upper Extremity Stability Test (CCKUE), the Functional Throwing Performance Index (FTPI) and the Seated Shot Put Functional Test (SSPT) were used for functional testing, whilst power in abduction, external rotation, and internal rotation was assessed. The Sports section of the DASH score and the Constant score were used. These were obtained at the beginning of the study period. The participants were divided into two groups, the study group, and the control group. The study group underwent daily home stretches (Sleeper’s stretch and Pectorals minor stretch) and strengthening exercises (external rotation and forward flexion in a side-lying position, horizontal abduction in the prone position). Follow up with functional testing, strength testing and scores was done at four monthly intervals for one year. Results: The pain was reported in 3 athletes in the control group compared to 1 in the study group (p=0.59). There was a larger improvement in athletes treated with prehabilitation when assessing external rotation (p=0.01) and internal rotation (p=0.03) when compared to the control group. There was no difference between groups in functional testing, scores and abduction strength. Conclusions: Prehabilitation in asymptomatic water polo players does not reduce the incidence of shoulder pain. The power of external rotation and internal rotation of the dominant improved more in athletes who performed prehabilitation.